An integrative review of case study methodologies in occupational therapy publications/ Revisão integrativa sobre a metodologia dos estudos de caso publicados na terapia ocupacional - Carey, Helen (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: The philosophy and practice of occupational therapy is subjective and this provides a challenge in reflecting the essence of practice within research methodologies for this profession. The individualistic practice of client centredness and the importance of context are core elements of occupational therapy. Objective: The aim is to conduct a descriptive analysis of contemporary use of case study research in occupational therapy based on selected articles using this methodology. Method: An integrative literature review was carried out to explore contemporary occupational therapy application of case study as an approach. The search comprised the publications between 2006-2016, containing the keywords: “case study method”, “case study approach” and “case study methodology” were combined with “occupational therapy” in the following databases: CINAHL, MEDLINE and PSYCHINFO, and Royal College of Occupational Therapistsonline dissertation database. Results: Thirty-two papers were synthesised; the studies predominantly featured mixed method data gathering as would be expected within a case study approach. There was a global uptake of the case study approach; UK, Canada, USA, Australia, Qatar, Brazil and Hong Kong in order of incidence. There was a relatively equal division between explanatory case studies and exploratory case studies. Conclusion: The case study approach is a strongly viable and acceptable research tool to reflect the elements of occupational therapy practice and enhance the evidence-based practice of this profession. Occupational therapy research would benefit from a higher number of case study designs to reflect the complexity, subjectivity and person centredness of the profession.